2022
DOI: 10.15184/aqy.2022.114
|View full text |Cite
|
Sign up to set email alerts
|

Climate change adaptation policy and planning for cultural heritage in low- and middle-income countries

Abstract: Climate change threatens archaeological sites and cultural landscapes globally. While to date, awareness and action around cultural heritage and climate change adaptation planning has focused on Europe and North America, in this article, the authors address adaptation policy and measures for heritage sites in low- and middle-income countries. Using a review of national adaptation plans, expert survey and five case studies, results show the varied climate change adaptation responses across four continents, thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As discussed by Fatorić and Seekamp (2017b), however, there remains a widespread lack of planning for adaptation to climate change. In this special section, Daly and colleagues (2022) present the results of the first study of the integration of cultural sites into the climate change adaptation plans of low- and middle-income countries. Their study uses a combination of a literature review and an expert-developed questionnaire sent out to 52 low- and middle-income countries that had named climate change ‘focal points’ on their International Council on Monuments and Sites national committees.…”
Section: Responding To the Impacts Of Climate Changementioning
confidence: 99%
“…As discussed by Fatorić and Seekamp (2017b), however, there remains a widespread lack of planning for adaptation to climate change. In this special section, Daly and colleagues (2022) present the results of the first study of the integration of cultural sites into the climate change adaptation plans of low- and middle-income countries. Their study uses a combination of a literature review and an expert-developed questionnaire sent out to 52 low- and middle-income countries that had named climate change ‘focal points’ on their International Council on Monuments and Sites national committees.…”
Section: Responding To the Impacts Of Climate Changementioning
confidence: 99%
“…Globally, climate change is already adversely affecting tangible and intangible cultural heritage and these impacts are projected to increase over time (Daly et al, 2022;Fatori c & Seekamp, 2017;Nicu & Fatori c, 2023;Orlove et al, 2022;Pearson et al, 2021;Simpson et al, 2022). Therefore, it could be argued that climate change should now be a primary lens through which conservation and management of cultural heritage is viewed.…”
Section: Introductionmentioning
confidence: 99%
“…Awareness of the need for natural and socioeconomic systems/sectors to reduce the impacts of climate change through climate adaptation processes has steadily increased globally (Berrang‐Ford et al, 2019; IPCC, 2022). Although the scientific community recognizes the importance of climate adaptation measures for tangible and intangible cultural heritage, there is little evidence that the cultural heritage sector has adapted to climate change (Brooks et al, 2020; Daly et al, 2022; Nicu & Fatorić, 2023; Shepherd et al, 2022; Simpson et al, 2022). A recent International Council on Monuments and Sites (ICOMOS) survey on the integration of cultural heritage into climate change policy showed that the lack of coordination and recognition of cultural heritage adaptation within climate change planning and policymaking is a global problem (Daly et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation